Editorial - Miranda Arguedas, Alice (1991)
14 years ago right here-not in this building that was just in our dreams, but this corner of the planet we call Heredia, we express our faith in other professional librarian:. one that was sensitive to the news and feel like driving their ethical duty to report the truth, to confront different opinions to you to let him seek the truth.